2019
DOI: 10.3393/ac.2018.10.01
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio: A Predictive Marker for Treatment Outcomes in Patients With Rectal Cancer Who Underwent Neoadjuvant Chemoradiation Followed by Surgery

Abstract: Purpose In this study, we investigated the role of neutrophil to lymphocyte ratio (NLR) as a predictor of tumor response and as a prognostic factor in patients with rectal cancer who had undergone curative surgery after neoadjuvant chemoradiation therapy (nCRT). Methods Between January 2009 and July 2016, we collected 140 consecutive patients who had undergone curative intent surgery after nCRT due to rectal adenocarcinoma. We obtained the pre- and post-nCRT NLR by divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…Various cutoff values have been used to de ne elevated NLR in previous studies. Although some studies used cutoff values calculated by statistical methods, the reported NLR cutoff values on patients with rectal cancer who underwent nCRT are inconsistent [27][28][29][30]. In this study, a cut-off value of 3.20 for the pre-CRT NLR was signi cantly related to RFS.…”
Section: Discussionmentioning
confidence: 61%
“…Various cutoff values have been used to de ne elevated NLR in previous studies. Although some studies used cutoff values calculated by statistical methods, the reported NLR cutoff values on patients with rectal cancer who underwent nCRT are inconsistent [27][28][29][30]. In this study, a cut-off value of 3.20 for the pre-CRT NLR was signi cantly related to RFS.…”
Section: Discussionmentioning
confidence: 61%
“…NLR consists of a combination of neutrophils and lymphocytes, and anti-tumor activity and activation of the inflammatory response impact this ratio [ 30 , 31 ]. Low NLR levels are associated with higher tumor response [ 30 , 32 ]. Like NLR, PLR is also a considerable marker of the inflammatory response, and anti-tumor efficacy and treatment response is better at low PLR levels in locally advanced rectal cancer [ 17 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous other studies that have utilized NLR to assess prognostic outcome in colorectal cancer. Jeon BH et al [15] used NLR to assess predictive outcomes in patients with rectal cancer who underwent chemotherapy followed by surgery and found that preoperative elevated NLR was independently associated with decreased five-year disease-free survival. Mazaki J et al [16] and Dell'Aquila E et al [17] showed that an elevated NLR is an important prognostic marker in advanced colorectal disease.…”
Section: Discussionmentioning
confidence: 99%